2004
DOI: 10.1111/j.1742-1241.2004.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Does carboxymethylcellulose have a role in reducing time to full enteral feeds in preterm neonates?

Abstract: The efficacy of prophylactic carboxymethylcellulose (CMC) in reducing the time to reach full enteral feeds (FEFs) in neonates <32 weeks' gestation was studied in a clinical trial. When ready for feeds, enrolled neonates were allocated to either CMC (dose: CMC content of 12 mg oral erythromycin ethyl succinate syrup, 6 hourly) or placebo till either maximum 10 days treatment or FEF (150 ml/kg/day) was reached. A standardised regimen guided enteral feeding. Demographic characteristics of enrolled neonates (CMC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…Of the 3 prophylactic RCTs ( table 1 ) [10][11][12] , 2 studies did not demonstrate any benefit of erythromycin as an effective prokinetic agent [10,11] . In addition, the objective of the RCT by Stenson et al [10] primarily concerned the use of intravenous erythromycin for eradication of Ureaplasma urealyticum and prevention of chronic lung disease.…”
Section: Review Of Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 3 prophylactic RCTs ( table 1 ) [10][11][12] , 2 studies did not demonstrate any benefit of erythromycin as an effective prokinetic agent [10,11] . In addition, the objective of the RCT by Stenson et al [10] primarily concerned the use of intravenous erythromycin for eradication of Ureaplasma urealyticum and prevention of chronic lung disease.…”
Section: Review Of Rctsmentioning
confidence: 99%
“…To date, 10 RCTs have reported effects of erythromycin on preterm newborns [10][11][12][13][14][15][16][17][18][19] . Seven RCTs used erythromycin as a rescue treatment [13][14][15][16][17][18][19] and 3 studies used the medication as a prophylactic prokinetic agent [10][11][12] . The characteristics of the study populations and findings of these RCTs are summarized in tables 1 and 2 .…”
Section: Review Of Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that 0.75 mg of intravenous erythromycin significantly increased antral motility of the stomach in neonates less than 30 weeks of gestation [1], thus showing functioning motilin receptors. Previous randomised controlled trials using antimicrobial doses (12 mg/kg/6-8-hourly) of erythromycin have failed to demonstrate a beneficial effect on the establishment of full feeds in preterm neonates [7][8][9]. On the other hand in a small study [10] again using antimicrobial doses, a beneficial effect on gastrointestinal dysmotility was observed in 7 preterm infants.…”
Section: Discussionmentioning
confidence: 88%
“…A number of studies carried out to investigate the prokinetic action of erythromycin in children (7) have obtained considerable evidence that the drug may be a useful prokinetic agent in feeding intolerance associated with prematurity, in low birth weight infants recovering from abdominal surgery, and in older children with a variety of other gastrointestinal disorders (8)(9)(10)(11). Only one randomized placebo-controlled trial has been conducted (12) and there are no clinical studies on the use of erythromycin in children with constipation.…”
mentioning
confidence: 99%